Selection into financial literacy programs: Evidence from a field study - Stephan Meier; Charles Sprenger (Federal Reserve Bank of Boston, 2007)
As financial literacy has been shown to correlate with good financial decisions, policymakers promote educational programs to improve individuals' financial decisions. But who selects into educational programs and who acquires information about personal finance? This paper, in a field study with more than 870 individuals, offers individuals free information about their credit reports (and credit scores). About 55 percent choose to participate in this small counseling program. To test whether those who self-select to acquire information about personal finance differ from those who do not on (normally) unobservable characteristics, we elicit time preferences, using incentivized choice experiments. Our results show that the two groups differ sharply in their discount factors: those who choose to acquire information do not discount the future as much as those who choose not to acquire information. This result has implications for financial education programs.
Keywords: D14; D91; C93; 330; Finanzwissen; Bildungsverhalten; Zeitpräferenz; USA